Mathematische Stochastik: 09.03. - 15.03.1997 - Gärtner, Jürgen; Gill, Richard D.; Mammen, Enno (Tagungsbericht, 1997)
Gerard Ben Arous; Rudolf Beran; Philippe Biane; Erwin Bolthausen; Anton Bovier; Olivier Catoni; Francis M. Comets; Jean Dominique Deuschel; Paul Doukhan; Lutz Dümbgen; Martin E. Dyer; Peter Eichelsbacher; Jürgen Franke; Jürgen Gärtner; Ursula Gather; Hans-Otto Georgii; Giambattista Giacomin; Richard D. Gill; Evarist Gine; Friedrich Götze; Rudolf Grübel; Malte Grunwald; Wolfgang Härdle; Marc Hallin; Frank den Hollander; Achim Klenke; Wolfgang D. König; Jens-Peter Kreiß; Claudio Landim; Boris Y. Levit; Mark Low; Matthias Löwe; Enno Mammen; James Stephen Marron; Dietrich Werner Müller; Yoichi Nishiyama; Michael Nussbaum; Yosihiko Ogata; Emmanuel Rio; Hermann Rost; Vladimir G. Spokoiny; Jeffrey Steif; Helmut Strasser; Winfried Stute; Howell Tong; Alexandre B. Tsybakov; Aad W. van der Vaart; Anton Wakolbinger; Willem R. van Zwet